Extracellular vesicles in arbovirus infections: from basic biology to potential clinical applications - Tiberti, Natalia; Castilletti, Concetta; Gobbi, Federico Giovanni (Frontiers in Cellular and Infection Microbiology, 2025)
Arthropod-borne viruses, or arboviruses, are currently considered a global health threat responsible for potentially severe human diseases. The increased population density, changes in land use and climate change are some of the factors that are contributing to the spread of these infections over the last years. The pathogenesis of these diseases and the mechanisms of interaction with the host, especially those leading to the development of severe forms, are yet to be fully understood. In recent years extracellular vesicles (EVs) have emerged as important players in the inter-cellular and host-pathogen interaction arising a lot of interest also in the field of vector-borne viruses. In this context, EVs seem to play a dual role, by either promoting, thus facilitating, or preventing infection. Many studies are showing how viruses can hijack the vesiculation machinery to escape the host immune response and exploit EVs to sustain their replication and propagation, even though EVs shed by immune cells seem essential to promote antiviral responses. In this manuscript we reviewed the current knowledge regarding the association between EVs and vector-borne viruses, paying particular attention to their possible role in disease transmission and dissemination, as well as to their potential as novel tools for clinical applications, spanning from biomarkers of clinical utility to novel therapeutic options.